Quality of life and its associated factors among women diagnosed with pelvic organ prolapse in Gynecology outpatient department Southern Nations, Nationalities, and Peoples region public referral hospitals, Ethiopia - Zewdu Tefera; Belsity Temesgen; Mikyas Arega; Tmesgen Getaneh; Aynalem Belay (BMC, 2023)
Abstract Background Pelvic organ prolapse is an important public health issue that influences millions of women's lives; through limitations on physical, social, and sexual activities as well as psychological distress. However, there were no reports on the quality of life for women with pelvic organ prolapse in Ethiopia. Therefore this study amid to assess the magnitude of quality of life and its associated factors among women who diagnosed with pelvic organ prolapse in Gynecology outpatient departments in Southern Nations, Nationalities, and Peoples region public referral hospitals; Ethiopia. Method An institutional-based cross-sectional study was conducted in Southern Nations, Nationalities, and Peoples region of public referral hospitals from May 1-July 4, 2022 among 419 diagnosed women with pelvic organ prolapse. A validated tool was used to collect the data. The collected data were entered into Epidata version 3.1 and analyzed using the Statistical Package for Social Sciences. Bivariable and multivariable logistic regression was computed. The p-value of < 0.05 was used to declare the final statistical significance. Result A total of 409 women with pelvic organ prolapse were included in the study, giving a response rate of 97.6%. The overall poor quality of life was 57.5%. Regarding the quality of life domains; personal relationships (73.6%), were highly affected, and sleep/energy (24.2%) was the least affected domain. Stage III/IV prolapse (AOR = 2.52, 95% CI: 1.34, 4.74), menopause (AOR = 3.21, 95% CI 1.75, 5.97), unmarried women (widowed, divorced) (AOR = 2.81, 95% CI: 1.48, 5.32), and longer duration of prolapse (AOR = 5.8, 95% CI: 3.13, 10.81), were significantly associated with poor quality of life. Conclusion More than half of women with pelvic organ prolapse had a poor quality of life. Stage III/IV prolapse, longer duration of prolapse, menopause women, and unmarried women are statistically significant factors for the quality of life of women with Pelvic organ prolapse.